A high-strength lightweight concrete made using straw. Issue 9 (15th November 2019) - Kammoun, Zied; Trabelsi, Abderraouf
Abstract : This experimental work aims to develop an eco-lightweight concrete with excellent mechanical and thermophysical properties using straw. Thus, this paper considers the use of a formulation of an ultrahigh-performance concrete based on dune sand, with the introduction of up to 20 kg/m 3 of straw. The study investigates the mechanical and thermophysical properties of the obtained high-strength lightweight concrete and examines the effects of the straw length. The results show that, depending on the amount of straw used, a decrease of up to 33% of density and 60% of thermal conductivity is noted. Moreover, despite increasing the straw content, which reduces the mechanical strength of the concrete, interesting strength values are noted; for instance, values varying from 42 to 59 MPa in compressive strength and from 3·2 to 5·3 MPa in flexural strength for 2 cm of straw length are obtained.